Hubungan Stres Akademik Peserta Didik Dengan Hasil Belajar Biologi - Sainab, Sainab (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Academic stress is a situation where students cannot face academic demands, there are many tasks and obligations that must be fulfilled by students at school, this can cause stress for students. The research objective was to determine the relationship between academic stress and student learning outcomes. This research is a correlational research. The sampling technique was carried out by using saturated sampling technique. So that the sample used was 37 people. Learning outcomes data obtained throughdocumentation of learning outcomes. The research data were analyzed using SPSS 23. The results showed that there was a significant relationship between academic stress and biology learning outcomes for class XI MIA MAN 1 Majene students with a sig. 0.032 <0.05, 3).